Comparison of the diagnostic capabilities of tNGS and mNGS for pathogens causing lower respiratory tract infections: a prospective observational study - Ding, Yuchen; Jing, Chuwei; Wei, Jiachen; Wang, Danni; Li, Wen; Wang, Mingyue; Zhou, Ji; Qian, Qian; Sun, Wenkui (Frontiers in Cellular and Infection Microbiology, 2025)
AimsPathogens in lower respiratory tract infections(LRTI) are complex. Conventional microbiological testings(CMTs) are time-consuming and inaccurate. mNGS is widely used to overcome these issues. tNGS, as an emerging NGS technology, has uncertain diagnostic efficacy.Materials and methods136 suspected LRTI patients were included from January 2022 to February 2024 from the Department of Respiratory and Critical Care Medicine at Jiangsu Province People’s Hospital,China.We simultaneously submitted the bronchoalveolar lavage fluids (BALFs) for mNGS, tNGS and conventional microbial testing (CMTs) and compared the pathogen diagnostic efficacy of mNGS, and tNGS.ResultsA total of 136 patients were included, and there was no statistically significant difference in the detection sensitivity(74.75% VS 78.64%, p>0,05) and specificity(81.82% vs 93,94%,p>0.05) between mNGS and tNGS. However, tNGS has a higher sensitivity(27.94% vs 17.65%,p=0.043)and specificity(88.78% vs 84.82%,p=0.048) for fungi. According to our diagnostic criteria, tNGS successfully identified 3 cases of Pneumocystis jirovecii(P. jirovecii) individually. In addition, both tNGS and mNGS detected chlamydia psittaci whereas CMTs were unable to detect it.ConclusionstNGS demonstrates diagnostic efficacy for pathogens in lower respiratory tract infections that is comparable to mNGS. However, tNGS has specific advantages in the detection of fungi. Considering the cost-effectiveness of tNGS, it is recommended to implement tNGS clinically for patients with lower respiratory tract infections.